2004
DOI: 10.1128/cdli.11.3.625-626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Arg677Trp Polymorphism Is Associated with Susceptibility to Tuberculosis in Tunisian Patients

Abstract: Toll-like receptor 2 (TLR2) is critical in the immune response to mycobacteria. Herein, we report that the frequency of a human TLR2 Arg677Trp polymorphism (C2029T nucleotide substitution) in tuberculosis patients in Tunisia is significantly higher than in healthy controls (P < 0.0001). This finding suggests that this polymorphism could be a risk factor for tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
5
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(164 citation statements)
references
References 14 publications
2
149
5
8
Order By: Relevance
“…The Arg753Gln polymorphism has been associated with a negative influence on TLR2 signalling, increasing the risk of mycobacterial infections (Mycobacterium leprae and Mycobacterium tuberculosis) as well as infections with Gram-positive (Staphylococcus aureus) and Gram-negative (Borrelia burgdorferi) bacteria (Lorenz et al, 2000;Ogus et al, 2004). The Arg677Trp mutation is probably involved in determining the type of leprosy, because it was significantly more prevalent in patients with lepromatous leprosy than with tuberculoid leprosy (Kang and Chae, 2001;Ben-Ali et al, 2004). Both mutations are located at the C-terminus of the TLR2, in the TIR .…”
Section: Discussionmentioning
confidence: 99%
“…The Arg753Gln polymorphism has been associated with a negative influence on TLR2 signalling, increasing the risk of mycobacterial infections (Mycobacterium leprae and Mycobacterium tuberculosis) as well as infections with Gram-positive (Staphylococcus aureus) and Gram-negative (Borrelia burgdorferi) bacteria (Lorenz et al, 2000;Ogus et al, 2004). The Arg677Trp mutation is probably involved in determining the type of leprosy, because it was significantly more prevalent in patients with lepromatous leprosy than with tuberculoid leprosy (Kang and Chae, 2001;Ben-Ali et al, 2004). Both mutations are located at the C-terminus of the TLR2, in the TIR .…”
Section: Discussionmentioning
confidence: 99%
“…10 TLR2 interacts with M. tuberculosis cell-wall components to induce cellular activation, killing of intracellular microbes and apoptosis, 11 and coding genomic variation in TLR2 has been associated with active TB. 12,13 TLR4 was initially identified as the mediator of lipopolysaccharide (LPS) inflammatory responses 14 and interacts with both a heat-labile soluble mycobacterial factor and whole viable M. tuberculosis to trigger innate responses. 15,16 M. tuberculosis-induced tumor necrosis factor and nitric-oxide production can be blocked by the LPS lipid A antagonist E5531, 17 and it has been shown that Tlr4-deficient mice develops a chronic lung infection resembling human disease when exposed to aerosolized M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…27 That TLR2-deficient mice are highly susceptible to M. tuberculosis infection 28,29 suggests that mutations that affect TLR2 expression may impair host response to this pathogen. Although missense mutations in the coding sequence of the human TLR2 gene have been associated with TB, 30,31 there are no reports of association between promoter polymorphisms of this gene and TB. The aim of this study was to evaluate the association between the guanine-thymine (GT) repeat microsatellite polymorphisms in intron II of the human TLR2 gene, which we previously reported, 32 and the presence of TB in the Korean population, which has reasonable genetic homogeneity.…”
Section: Introductionmentioning
confidence: 99%